3D electromagnetic tomography using a single layer sensor array. (March 2021) - Yue, Yuanli; Liu, Ze; Miao, Yu; Pan, Jiaqi
Abstract: Electromagnetic tomography (EMT) is a non-invasive technique to gain the induced voltages and to reconstruct the distribution of electromagnetic properties. A volume imaging using a single layer sensor array, namely, Single Layer 3D-EMT, has been developed in this paper. To solve the forward problem, three kinds of sensor arrays are established with different number of coils, —8, 12 and 16, to conduct simulations. Four typical conductivity distributions are used to verify the 3D-EMT imaging with single layer sensor array. The calculation of sensitivity maps in 3D views is presented, and the sensitivity maps of different layers, from z = 0 to z = 20, are analyzed. The conjugate gradient iterative method has been adopted in image reconstruction. It can be seen from the simulation results that the 3D reconstructed images using a single layer sensor array can display the distribution of the measured objects in position, shape, and size. By calculating the relative error, the quality of the reconstructed images is evaluated andthe result shows that the 12-coil sensor array has the best image quality among three sensor arrays. In addition, the single layer 3D experimental system has been established to evaluate the effectiveness of 3D imaging using a single layer sensor array. In order to save the hardware resources, the paper presents the author's research work about the possibility of Single Layer 3D-EMT imaging in simulations and experiments. This can also provide a guide to explore the potential application with electromagnetic testing technique. Highlights: A volume imaging using a single layer sensor array, namely, Single Layer 3D-EMT, has been developed in this paper. The 3D sensitivity maps calculation is presented in 3D views. Different layers of sensitivity maps are analyzed. The experiments are demonstrated, and the results confirmed the feasibility of 3D imaging using a single layer sensor array. This paper presents that Single Layer 3D-EMT can save the hardware resources without increasing the number of sensors.